2014
DOI: 10.1177/0300985814521248
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Mechanisms Underlying the Clinical Findings in Canine Leishmaniosis due to Leishmaniainfantum/chagasi

Abstract: In dogs with symptomatic or asymptomatic leishmaniosis, Leishmania infantum appears to induce a mixed Th1/Th2 immune response that in the sick dog may eventually result in tissue damage via different pathomechanisms, notably granulomatous inflammation (eg, nodular dermatitis, osteomyelitis), immune complex deposition (eg, glomerulonephritis), and/or autoantibody production (eg, polymyositis). This is a compensatory but detrimental mechanism generated mainly because of the insufficient killing capacity of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(163 citation statements)
references
References 134 publications
(201 reference statements)
6
141
1
15
Order By: Relevance
“…Our results are in accordance with Poli et al [21] who, in a study of glomerular lesions in dog with CanL, found no correlation between renal involvement and anti- Leishmania titer and creatinine but found correlation between glomerular lesions and the amount of proteinuria. Glomerulopathy that characterized CanL causes proteinuria due to deposition of circulating antigen/antibody complexes; this fact may explain the correlation between UP/UC and IgG value found in our study [18]. Renal damage with less than 75 percent of nonfunctional nephrons may not cause increase of serum creatinine concentration [22]; therefore, elevation of this parameter during CanL may show up later than the presence of protein in the urine.…”
Section: Discussionmentioning
confidence: 78%
“…Our results are in accordance with Poli et al [21] who, in a study of glomerular lesions in dog with CanL, found no correlation between renal involvement and anti- Leishmania titer and creatinine but found correlation between glomerular lesions and the amount of proteinuria. Glomerulopathy that characterized CanL causes proteinuria due to deposition of circulating antigen/antibody complexes; this fact may explain the correlation between UP/UC and IgG value found in our study [18]. Renal damage with less than 75 percent of nonfunctional nephrons may not cause increase of serum creatinine concentration [22]; therefore, elevation of this parameter during CanL may show up later than the presence of protein in the urine.…”
Section: Discussionmentioning
confidence: 78%
“…In sick dogs, the depletion of T lymphocytes in lymphoid organs becomes falsely compensated B-cell proliferation and activity (Koutinas and Koutinas, 2014). This activity, along with the activity of plasma cells, histiocytes and macrophages, potentially explains the generalized lymphadenomegaly, splenomegaly and hyperglobulinemia, which have become clinical hallmarks of this disease (Baneth et al 2008; Koutinas and Koutinas, 2014).…”
Section: T Cell Mediated Immunity Including Regulatory T Lymphocytesmentioning
confidence: 99%
“…However, other less typical manifestations such as papular dermatitis, muco-cutaneous nodular dermatitis or sterile pustular dermatitis are also diagnosed [5, 6]. This clinical variation is due to a wide variety of pathological mechanisms occurring secondarily to the inflammation, immune complex deposition and/or autoantibody production [7] and to the genetically determined or acquired inability of the immune system to control parasite multiplication and tissue invasion [8]. …”
Section: Introductionmentioning
confidence: 99%